PELATIHAN PEMBUATAN PUPUK ORGANIK GRANUL (POG) BERBAHAN BAKU SLUDGE LUARAN DIGESTER BIOGAS SEBAGAI UPAYA PENGOPTIMALAN PEMANFAATAN DIGESTER BIOGAS PEDESAAN - Nawansih, Otik; Damayanti, Sri Ismiyati; Taharuddin; Iryani, Dewi Agustina; Haviz, Muhammad; Ginting, Simparmin Br (Nemui Nyimah, 2024)
The solid bioslurry fertilizer (sludge) produced by the biogas digester has good quality, but is still less attractive to farmers because it is in bulk form. Therefore, it is necessary to carry out training regarding the granulation of sludge into granular organic fertilizer (POG). The long-term goal of this service is fertilizer independence at the farmer level, through the ability of farmers to process surrounding waste into more practical organic fertilizer. The specific target is that the public knows science and technology related to fertilizer granulation and has skills in granulating fertilizer. The methods used are: coordination of the lecturer team with the community regarding training activities, preparation of raw materials, namely sludge and compost made from sludge-coffee husk, socialization and discussion regarding fertilizer granulation science and technology, training in making POG, and evaluation of activities together with the community. Implementation of service begins with coordinating the lecturer team with the community regarding the implementation of activities, continues with the preparation of raw materials and tools with the assistance of residents and students, implementation of training with assistance from students by inviting pekon officials and the community, ending with an evaluation with the community to determine the sustainability of the program. The community is very interested in creating a village business with this organic fertilizer, which in the future can be managed by BUMDes. An obstacle during community service is the difficulty of gathering residents during the day due to various different activities.